Agritourism: Alternative for sustainable rural development - Apaza-Panca, Cynthia Milagros; Santa-Cruz Arévalo, Johanna Elena; Apaza-Apaza, Silverio (Dominio de las Ciencias, 2020)
Agritourism is regarded as one type of rural tourism and can be defined a sustainable activity that is developed in rural areas where has necessary features to offer such as touristic services which allow tourists to have a lively experience on culture, rural traditions. Be involved directly and have the chance to do daily rural chores by giving spaces for leisure and enjoyment and being in contact with nature. The aim of this review was to analyze and provide relevant scientific information about agritourism as an alternative for sustainable rural development. To this end, a systematic review was carried out and keywords like "agroturismo" in Spanish and "agrotourism", "agritourism" in English were researched and subsequently, at a first step a 55- article were assessed and which have been published from 1994 to 2020. Findings demonstrate in most countries, there are local agrotourism business initiatives that aim to promote the sustainability of economic and environmental activities, and are seen as a strategy to mitigate rural-to-urban migration, develop economic sustainability, generate employment and local identity. A better understanding of this process, rural development, agriculture and tourism have become an alternative that combines two elements, thus contributing to the social and economic development of the area; it protects the environment and generates employment opportunities, highlighting local women.